Legal Disinformation Challenges in the Digital Age - Fitri, Dwi; Ramadhani, Ulfa; Arafat, Yasir; Zuraini, Intan; Khairunnisa; S, Nadia Juniarti; Abdan, Muhammad (Indonesian Journal of Education and Social Humanities, 2025)
The spread of disinformation through digital media has emerged as a serious challenge to legal and social stability in Indonesia, particularly when it targets sensitive legal issues. Thedissemination of false information related to laws or legal processes not only disrupts public order but also erodes public trust in legal institutions. This study aims to analyze the challenges faced in enforcing the law against the spread of digital disinformation and to evaluate the effectiveness of existing regulations, especially Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law). Using a normative juridical method with a qualitative approach, the study identifies key obstacles, including the limited adaptability of regulations to technological developments, the low level of digital literacy among the public, and the complexity of tracing perpetrators in cyberspace. Based on these findings, the study recommends a comprehensive counter-strategy, which includes improving digital literacy, strengthening inter-agency collaboration among law enforcement institutions, and updating legal frameworks to be more responsive to the evolving digital landscape. Through this integrative approach, it is expected that law enforcement in the digital era can become more effective and provide better legal protection for the public. Keywords: digital disinformation, law enforcement, ITE Law, digital literacy, information technology regulation.